Design for snake robot motion via partial grasping on pipes. (16th February 2023) - Konishi, Ryoga; Nakajima, Mizuki; Tanaka, Kazuo; Matsuno, Fumitoshi; Tanaka, Motoyasu
Abstract : This paper proposes a method for the movement of a snake robot on crowded pipes or one with large branches. The robot moves along a pipe by grasping it with its entire body instead of wrapping around it, and it adjusts its body shape to the target curve. The proposed robot contains a part that does not contact the pipe, allowing it to move in two directions: along or around the pipe axis. It avoids obstacles by combining these movements while making contact with itself to reduce joint torque and preserve body shape. Experiments demonstrated the efficacy of the proposed robotic snake motion by circumnavigating an obstacle on a pipe in several situations. GRAPHICAL ABSTRACT: UF0001